1995
DOI: 10.1104/pp.108.3.1109
|View full text |Cite
|
Sign up to set email alerts
|

cis Elements and trans-Acting Factors Affecting Regulation of a Nonphotosynthetic Light-Regulated Gene for Chloroplast Glutamine Synthetase

Abstract: The glutamine synthetase (GS) gene family in pea (Pisum safivum) consists of four nuclear genes encoding distinct isoenzymes. Molecular studies have shown that the GS2 gene encoding chloroplastlocalized CS is expressed in specific cell types and is regulated by diverse factors such as light and photorespiration. Here, we present the nucleotide sequence of the pea GS2 gene promoter. To identify the elements involved in regulation of GS2 expression, GS2 promoter-deletion analyses were performed using GS2-GUS fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 24 publications
0
26
0
2
Order By: Relevance
“…The motif at position 2245 is similar to the binding site of SBF1, a transcriptional repressor (Lawton et al, 1991). On the other hand, motifs including ZC2 recognized by chromatin remodelers with zinc-finger domains (Ponte et al, 1994), telobox recognized by Athb homeodomain proteins (Sessa et al, 1993), W-box recognized by WRKY transcription factors (Eulgem et al, 2000), BOX1* (Tjaden et al, 1995), and GCCAAG motif (Leah et al, 1994) are reported to be involved in transcriptional activation. The predicted motif composition of the AtHDA7 promoter suggests that its transcription is regulated in a complex way.…”
Section: In Silico Analysis Of Athda7mentioning
confidence: 99%
“…The motif at position 2245 is similar to the binding site of SBF1, a transcriptional repressor (Lawton et al, 1991). On the other hand, motifs including ZC2 recognized by chromatin remodelers with zinc-finger domains (Ponte et al, 1994), telobox recognized by Athb homeodomain proteins (Sessa et al, 1993), W-box recognized by WRKY transcription factors (Eulgem et al, 2000), BOX1* (Tjaden et al, 1995), and GCCAAG motif (Leah et al, 1994) are reported to be involved in transcriptional activation. The predicted motif composition of the AtHDA7 promoter suggests that its transcription is regulated in a complex way.…”
Section: In Silico Analysis Of Athda7mentioning
confidence: 99%
“…Light responsive GS2 promoters were demonstrated for Phaseolus vulgaris (Cock et al 1992) and pea (Tjaden et al 1995). The GS2 pea promoter contains an AT-rich 33 bp region at 807 bp upstream of the transcription start site, and when this AT-rich region was deleted, expression was reduced 10-fold (Tjaden and Coruzzi 1994).…”
Section: Promotersmentioning
confidence: 99%
“…However, a direct linkage between gene expression and the light-signal transduction pathway is still absent. Some nitrogen assimilation gene promoters, including those of pea GS2 and AS, are known to possess light-responsive elements (Tjaden et al, 1995;F.-Y. Tsai (B) A portion of Figure 2A is enlarged to show that the changes in GLN2 and ASN1 mRNA levels under light and dark conditions are paralleled by changes in glutamine and asparagine levels (also see Table 2 and Figure 1).…”
Section: Light and Metabolic Control Of Amide Amino Acid Biosynthesismentioning
confidence: 99%